Determination of tamoxifen and its metabolites in human plasma by nonaqueous capillary electrophoresis with contactless conductivity detection. Issue 21 (1st September 2015) - Thang, Lee Yien; Shahir, Shafinaz; See, Hong Heng
Abstract : A new approach for the quantification of tamoxifen and its metabolites 4‐hydroxytamoxifen, N ‐desmethyltamoxifen, and 4‐hydroxy‐ N ‐desmethyltamoxifen (endoxifen) in human plasma samples using NACE coupled with contactless conductivity detection (C 4 D) is presented. The buffer system employed consisted of 7.5 mM deoxycholic acid sodium salt, 15 mM acetic acid, and 1 mM 18‐crown‐6 in 100% methanol. The complete separation of all targeted compounds (including endoxifen racemate) could be achieved within 6 min under optimized conditions. The proposed method was validated and showed good linearity in the range from 100 to 5000 ng/mL with correlation coefficients between 0.9922 and 0.9973, LODs in the range of 25–40 ng/mL, and acceptable reproducibility of the peak area (intraday RSD 2.2–3.1%, n = 4; interday (3 days) RSD 6.0–8.8%, n = 4). The developed method was successfully demonstrated for the quantification of tamoxifen and its metabolites in human plasma samples collected from breast cancer patients undertaking tamoxifen treatment.